1987
DOI: 10.1042/bj2410161
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic ratios of free [NADPH]/[NADP+] and [NADH]/[NAD+] in mouse pancreatic islets, and nutrient-induced insulin secretion

Abstract: When the extracellular concentration of glucose was raised from 3 mM to 7 mM (the concentration interval in which beta-cell depolarization and the major decrease in K+ permeability occur), the cytosolic free [NADPH]/[NADP+] ratio in mouse pancreatic islets increased by 29.5%. When glucose was increased to 20 mM, a 117% increase was observed. Glucose had no effect on the cytosolic free [NADH]/[NAD+] ratio. Neither the cytosolic free [NADPH]/[NADP+] ratio nor the corresponding [NADH]/[NAD+] ratio was affected wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…Alternatively, NADH enters the mitochondria via two shuttles (glycerol–phosphate and malate–aspartate shuttles) to produce ATP (Eto et al ., 1999; Hedeskov et al ., 1987; Malaisse et al ., 1979; Pralong et al ., 1990). Compared to most other mammalian cells, in β cells display high activities of the glycerol–phosphate shuttle and mitochondrial glycerol–phosphate dehydrogenase (mGPDH) suggesting an important role for NADH in β cell function (MacDonald et al ., 1990).…”
Section: Section IImentioning
confidence: 99%
“…Alternatively, NADH enters the mitochondria via two shuttles (glycerol–phosphate and malate–aspartate shuttles) to produce ATP (Eto et al ., 1999; Hedeskov et al ., 1987; Malaisse et al ., 1979; Pralong et al ., 1990). Compared to most other mammalian cells, in β cells display high activities of the glycerol–phosphate shuttle and mitochondrial glycerol–phosphate dehydrogenase (mGPDH) suggesting an important role for NADH in β cell function (MacDonald et al ., 1990).…”
Section: Section IImentioning
confidence: 99%
“…where c is the ratio between the volumes of the cytosolic and mitochondrial compartments, here assumed to amount to 20 (30,39). Finally, for the reproduction of the results of Eto et al (26), we need the glucose oxidation rate j GO, which we measure as j GO ϭ j GPDH Ϫ j LDH (6) and the flux via the dehydrogenases IDH (3 isoforms) and OGDH, j DH, which we measure as…”
Section: Study Outline and Measurementsmentioning
confidence: 99%
“…. ]tot indicates total cellular content normalized by the cytosolic volume, and where c is the ratio between the volumes of the cytosolic and mitochondrial compartments, here assumed to amount to ϳ20 (30,39). In the case of ME, the equilibrium constant had to be divided by the tissue partial pressure of carbon dioxide (2), which amounts to ϳ0.06 bar (6), and then multiplied by the NADPc/ NADPHc ratio.…”
Section: Equilibrium Constantsmentioning
confidence: 99%
“…Recent studies have strongly suggested that NADPH production via the malate-aspartate shuttle [162,163,164], also called pyruvate cycling [165], might be an important metabolic signal. Indeed, metabolisable insulin secretagogues increase the NADPH/NADP + ratio in rodent islets [166,167] and inhibition of NADPH formation reduces glucose-stimulated insulin secretion from rat islets [168,169]. Recent evidence suggests the existence of membrane associated aldehyde oxidoreductase-like enzyme activity in rat islets [170] and, as mentioned above, a number of oxidoreductase-like Kvβ subunits (Kvβ1, 2 and 3) are expressed in human and rat islets and INS-1 insulinoma cells [93].…”
Section: Regulation Of Kv Channel Activity In Beta Cellsmentioning
confidence: 99%